Reported health effects of passive smoking by bar workers in Ibadan, Nigeria - Modupe Onigbogi; Olanrewaju Onigbogi (Tobacco Induced Diseases, 2018)
Background Workplace exposure as occurs in indoor bars and restaurants in Nigeria are the major areas where workers get exposed to such. This survey was conducted to compare the immediate reported health problems between a selected group of indoor bar workers and outdoor bar workers and evaluate their perceptions of about the dangers of passive tobacco smoke.